1997
DOI: 10.1177/026765919701200307
|View full text |Cite
|
Sign up to set email alerts
|

Conventional haemofiltration during routine coronary bypass surgery

Abstract: The use of conventional ultrafiltration during cardiopulmonary bypass (CPB) has been well recognized as an efficient modality of therapy to reverse the effects of deliberate haemodilution. Routine use of the haemofilter was prospectively studied on 60 patients undergoing coronary artery bypass surgery. Group A consisted of 30 patients on whom the ultrafiltrator was used and compared to group B who did not receive the ultrafiltration technique. The COBE 1200 ultrafiltration device was used. The results of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 15 publications
1
16
0
7
Order By: Relevance
“…Few studies in cardiac surgery have focused, let alone reported, on the relationship between CUF and postoperative kidney injury [5,6]. Babka and colleagues [5] randomly assigned 60 patients undergoing CABG surgery to receive CUF.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies in cardiac surgery have focused, let alone reported, on the relationship between CUF and postoperative kidney injury [5,6]. Babka and colleagues [5] randomly assigned 60 patients undergoing CABG surgery to receive CUF.…”
Section: Commentmentioning
confidence: 99%
“…Conversely, CUF may have an adverse consequence on kidney injury, mechanistically related to fluid shift imbalances and renal hypoperfusion. A few relatively small studies have explored the short-term risks associated with CUF, and have assessed kidney injury in a number of ways, including renal insufficiency, creatinine clearance (CrCl), and elevated postoperative creatinine [4][5][6][7]. Three of these studies were randomized trials [4][5][6]; two reported no significant difference associated with CUF in terms of renal insufficiency [4,5], whereas one reported a significantly lower adjusted 24-hour creatinine associated with CUF [6].…”
mentioning
confidence: 99%
“…This opinion is not supported by evidence from this study and other similar studies where the patterns of HCT were found to be similar. 61,62 Evidence from a recent meta-analysis also supports the idea that the need for blood transfusions is significantly reduced by ultrafiltration during cardiac surgery. 63 In addition, evidence from the latter study 62 also demonstrated that the platelet count after bypass was not significantly different from that in the non-haemofiltration group, an observation that is also in agreement with our findings.…”
Section: Adverse Events and Overall Safety Of Intraoperative Zero-balmentioning
confidence: 92%
“…Among these options, studies have shown that routine use of hemofiltration and/ or cell saver improves the quality of surgical care [4][5][6].…”
Section: Introductionmentioning
confidence: 99%